2015
DOI: 10.1016/j.neuron.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Early- and Late-Born Parvalbumin Basket Cell Subpopulations Exhibiting Distinct Regulation and Roles in Learning

Abstract: Brain networks can support learning by promoting acquisition of task-relevant information or by adhering to validated rules, but the mechanisms involved are poorly understood. Upon learning, local inhibitory parvalbumin (PV)-expressing Basket cell networks can switch to opposite configurations that either favor or interfere with further learning, but how this opposite plasticity is induced and relates to distinct learning requirements has remained unclear. Here, we show that PV Basket cells consist of hitherto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(124 citation statements)
references
References 50 publications
(88 reference statements)
8
114
0
Order By: Relevance
“…Likewise, only lateborn cells exhibited a corresponding Mef2a/inhibitory connectivity shift upon pharmacogenetic inhibition. These results provided evidence that persistent direct non-synaptic excitation or inhibition of PV neurons can shift PV expression values in all PV cells, but only early-born neurons exhibit Mef2a/connectivity plasticity upon excitation and only late-born neurons exhibit Mef2a/connectivity plasticity upon inhibition [22].…”
Section: Subpopulation Cell-plasticity Specifically Regulated Throughmentioning
confidence: 73%
See 3 more Smart Citations
“…Likewise, only lateborn cells exhibited a corresponding Mef2a/inhibitory connectivity shift upon pharmacogenetic inhibition. These results provided evidence that persistent direct non-synaptic excitation or inhibition of PV neurons can shift PV expression values in all PV cells, but only early-born neurons exhibit Mef2a/connectivity plasticity upon excitation and only late-born neurons exhibit Mef2a/connectivity plasticity upon inhibition [22].…”
Section: Subpopulation Cell-plasticity Specifically Regulated Throughmentioning
confidence: 73%
“…In complementary experiments tdTomato-positive E11.5 donor PV neurons transplanted into an E13.5 host exhibited high-and intermediate-high PV neurons values characteristic of their birthdate in donor E11.5 embryo. We concluded that PV and excitation/inhibition connectivity profiles of early-and late-born PV neurons in the adult reflect distinct intrinsic properties of these neurons determined at the time of neurogenesis [22].…”
Section: Subpopulations Of Pv Basket Cells Defined By Time Schedule Omentioning
confidence: 88%
See 2 more Smart Citations
“…Of note, Takesian and Hensch [15] have argued that the onset of critical periods in sensory and association cortices is determined by maturation of GABAergic circuits that regulate the developmental organization of neocortical, as well as HPC, circuits. Strong evidence supporting a specific role for PV - minimally as a biological marker of the state of GABAergic circuit functioning - has been provided in elegant studies conducted by Donato et al [29,70]. These studies have indicated that select populations of CA1 PV+ basket cells (both early- and late-born) differentially increase PV, which is dependent upon distinct learning requirements in mice.…”
Section: Discussionmentioning
confidence: 99%